2019
DOI: 10.1093/pm/pnz195
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Sensory Testing in Patients with Multisomatoform Disorder with Chronic Pain as the Leading Bodily Symptom—a Matched Case–Control Study

Abstract: Objective Chronic pain is a debilitating condition of multifactorial origin, often without physical findings to explain the presenting symptoms. Of the possible etiologies of persisting painful symptoms, somatoform disorders and functional somatic syndromes (FSS) are among the most challenging, with a prevalence of 8–20%. Many different somatoform disorders and FSS have overlapping symptoms, with pain being the most prevalent one. The concept of multisomatoform disorder (MSD) has been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Diagnostic criteria for MSD according to the Diagnostic and Statistical Manual of Mental Disorder-IV (DSM-IV) were fulfilled by all patients. As previously reported, there were no differences between gender and age ( p > 0.05) (control group: mean age, 52.1 ± 9.9 years; 73% women and 27% men; MSD group: mean age, 54.4 ± 10.1 years; 82% women and 18% men) [ 6 9 , 21 ]. As expected the physical component summary score of the SF-36 demonstrated a significant difference between patients and controls (28.75 ± 7.81 vs 54.0 ± 5.74) ( p < 0.0001).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Diagnostic criteria for MSD according to the Diagnostic and Statistical Manual of Mental Disorder-IV (DSM-IV) were fulfilled by all patients. As previously reported, there were no differences between gender and age ( p > 0.05) (control group: mean age, 52.1 ± 9.9 years; 73% women and 27% men; MSD group: mean age, 54.4 ± 10.1 years; 82% women and 18% men) [ 6 9 , 21 ]. As expected the physical component summary score of the SF-36 demonstrated a significant difference between patients and controls (28.75 ± 7.81 vs 54.0 ± 5.74) ( p < 0.0001).…”
Section: Resultssupporting
confidence: 63%
“…In a population-based twin study, genetic influences have been shown to play a role especially in painful FSS, whereas inconsistent results suggest a role of single nucleotide polymorphisms (SNPs) of serotonergic and dopaminergic genes [ 6 8 ]. Our group recently demonstrated common sensory alterations through quantitative sensory testing in patients with MSD [ 9 ] similar to those found in patients with fibromyalgia (FMS) [ 10 , 11 ]. In this context, the construct of chronic widespread pain is of particular interest.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Subjects. The patient collective was previously investigated regarding the role of single nucleotide polymorphisms [6][7][8] as well as the difference in quantitative sensory profiles and epigenetic regulation of TRPA1 expression between patients and controls [9,11]. Altogether, 300 individuals were recruited to participate (151 patients, 149 controls).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggest a role of SNPs in serotonergic and dopaminergic but not catecholamine-o-transferase genes in the etiology of MSD [6][7][8]. Patients with MSD and pain as the leading bodily symptom show characteristic sensory alterations as demonstrated through quantitative sensory measurements [9]. In human physiology, a complex interplay between an acute and chronic response to stress, hormonal regulation of homoeostasis, and neurotrophic factors exists.…”
Section: Introductionmentioning
confidence: 99%